Aula digital : impactos e desafios para escolas do município de Santa Luzia do Itanhi/SE - Dias, Robson Cledson de Jesus (2020)
The world is changing very fast as a result of na accelerated technological development. The benefits that new technologies generate are numerous and extend to each of the social sectors. In relation to education we can mention, for example, the importance of using the computer as a pedagogical resource that can boost the access to knowledge. However, there are some challenges. In order to understand the impacts and challenges caused by these technologies, it induced our interest in analyzing the process of implementing the Digital Classroom Project in Santa Luzia do Itanhi, its impacts and challenges in the teacher's pedagogical practice.The methodology adopted is qualitative, descriptive and has a case study as a way to carry out the research. Documents produced by international organizations were also used, as well as official documents that structure the Digital Classroom Project. The Municipal School of Elementary Education Edmar José da Cruz was adopted as a locus for this research, in that city, in the south of Sergipe. As collection instruments, semi-structured interviews and observation were used. The research subjects were the school teachers in question. After the entire investigation process, the results showed that the Digital Classroom Project, contemplated by educational policies, contributes to the improvement of educational practices, however there are some challenges to be overcome, such as the lack of appropriation of technology by the teacher and also the lack of effective monitoring that corresponds with the project proposal.